A triadic link between knowledge management, information technology and business strategies. Issue 2 (1st May 2017) - Venkitachalam, Krishna; Ambrosini, Véronique
Abstract: The extant literature shows that the connection between KM strategy and business strategy and business strategy and IT strategy has been extensively studied. However, the link between KM strategy and IT strategy remains unclear. To better understand how KM strategy influences IT strategy and vice versa within the context of business strategy, we synthesize the literature and contribute to the conceptualization of a triadic connection of the influences between business, KM and IT strategies and its deeper understanding in determining efficacy of knowledge use in organizations.